EARLY DETECTION AND STIMULATION INTERVENTIONS OF GROWTH AND DEVELOPMENT IN CHILDREN CHARACTER FORMING: SYSTEMATIC REVIEW - Shafira Amiyanti, Nurul Fathia (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: Child development involves cognitive-language, sensory-motor, and social-emotional aspects, with recognition of the significance of non-cognitive domains in predicting long-term outcomes. Factors such as genetics, health, and environment play crucial roles, with disparities in development observed in children from disadvantaged backgrounds. Approximately 250 million children in low and middle-income countries are at risk of poor development due to poverty, undernutrition, and limited stimulation, but early nurturing care can mitigate these effects. Integrated early detection and stimulation interventions are gaining importance, offering a comprehensive approach to child growth and development, and understanding their characteristics is crucial for tailored, context-specific interventions. Method: This study followed the 2020 PRISMA guidelines to ensure research alignment with necessary standards for accuracy. Articles were retrieved from databases including PubMed and Google Sholar database in October 2023.  Result: The search strategy produced a total of 7 results. After a thorough evaluation of the full-text papers, we ultimately included five papers in the final analysis, consisting of four retrospective analysis and studies.    Conclusion: In summary, the study revealed significant associations between respondents' knowledge and attitudes with early child development practices. It also emphasized the importance of culturally relevant interventions and the involvement of extended family in fostering child development, particularly in disadvantaged regions.